INVESTIGATION OF STUDENTS’ PERCEPTION TOWARD E-LEARNING IN THE FIFTH SEMESTER OF ENGLISH LANGUAGE EDUCATION UNDIKSHA - Nopa, P; hadisaputra, I N P; Agustini, D A E (Journal of Psychology and Instruction, 2019)
This study aims to investigate students' perceptions of e-learning. This research was conducted to determine students' perceptions in the use of information technology, especially e-learning in classroom learning. The research data were collected at English Language Education of UNDIKSHA with 80 questionnaires. The outcomes of the study showed the majority of the students think e-learning is an innovative idea and must be encouraged. Hybrid learning, which is a combination of online learning and face-to-face learning, is the preferred mode of learning for the respondents.